PENGARUH SEDUHAN DAUN ALPUKAT TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Sumirat, widhi (Akademi Keperawatan Pamenang, 2013)
Currently shifting diet of community from traditional food menu which rich in fiber and nutrient to fast food which high fat content, salt, and calorie but poor in fiber and nutrients. Salt and saturated fat nutrients in fast food increase the risk of hypertension. Hypertension impact is earning happened stroke, heart attack, kidney disturbance, and eyes disturbance. One treatment deribved from herbs, which uses avocado leaves. Patient of hypertension in the community do not know the majority of the benefits of avocado leaves as lowering blood pressure. This research is to know influence of steep of avocado leaves to blood preasure to patient of hypertension Research Desain which is used in this research is